TEACHERS’ SELF-CARE STRATEGIES AND SUPERVISION AS A SELF-CARE ACTIVITY FOR TEACHERS - Liepina, Elina; Martinsone, Kristine (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Covid-19 pandemic has caused unprecedented challenges for teachers and the resources of teachers have been critically exhausted causing fatigue and burn-out. Self-care actualization and practice is one way to strengthen teachers' emotional health and resilience. Self-care is understood as engagement in activities to preserve or improve one’s own health and well-being, in particular during periods of stress. Supervision is one of the activities where teachers can receive professional support, minimize negative emotions and develop stress resilience. The aim of this study was to investigate teachers' self-care strategies and experts’ views on actualization of self-care strategies and supervision as a self-care activity within supervision. The research was executed in two stages - quantitative data analysis and qualitative interviews. In the quantitative part the participants of the research were 245 teachers in Latvia. Self-Care Strategies Questionnaire was used to collect answers and the 14 strategies were measured on a 4-point Likert scale. Self-care strategies were assessed on what is considered important and is attainable. The results showed that there are statistically significant differences between importance and attainability in all 14 self-care strategies. All strategies were assessed higher on importance than the attainability. Experts indicated that supervision should take place during working hours, be publicly funded, regular and carried out as long-term support.